Dynamic Governance and Good Governance: Synergy in Regional Financial Management - Inrawaty Gita; Bahrullah Akbar; Marja Sinurat; Meltarini (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Regional financial management plays a central role in realizing good governance and effective public service delivery. In Indonesia, the performance of regional financial management is measured through the Regional Financial Management Index (IPKD), which serves as an accountability tool and a benchmark for improving governance quality. This study aims to identify and analyze the application of dynamic governance in regional financial management, including its inhibiting and supporting factors, as well as to formulate an implementation model of dynamic governance within the Bekasi City Government. The objective is to improve the IPKD as mandated by the Ministry of Home Affairs Regulation Number 19 of 2020. A qualitative research design was employed using a governmental science methodology. Data were collected through observation, interviews, and documentation, with the Bekasi City Government serving as the research locus. The results indicate that dynamic governance, based on the dynamic capabilities framework, has not been carried out optimally, resulting in a suboptimal IPKD score.